Answer:
![(x^2-3^2)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-3%5E2%29%28x%2B3%29)
![(x-3)(x+3)(x+3)](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%28x%2B3%29)
![(x-3)(x+3)^2](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%5E2)
Step-by-step explanation:
Given
![(x^2-9)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-9%29%28x%2B3%29)
Required
Select 3 equivalent expressions
![(x^2-9)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-9%29%28x%2B3%29)
Express 9 as 3^2
--- This is one equivalent expression
Take
as difference of two squares
-- This is another equivalent expression:
Solving further:
becomes
-- This is another equivalent expression:
Hence, the equivalent expressions are:
![(x^2-3^2)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-3%5E2%29%28x%2B3%29)
![(x-3)(x+3)(x+3)](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%28x%2B3%29)
![(x-3)(x+3)^2](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%5E2)
I don't know if it could be the area of a square but x has to be 8.34. (ROUNDED)
<h2>
Answer:</h2>
The graph of the circle is given in the image attached
1 feet = 12 inches
1 min = 60 s
1 feet/min = 12 in/60 s = 1 in/5 s = 0.2 in/s
Answer:
![\sqrt{39}](https://tex.z-dn.net/?f=%5Csqrt%7B39%7D)
Step-by-step explanation:
I think the answer choices were supposed to be:
![\sqrt{3} , \sqrt{6} , \sqrt{39} , \sqrt{89}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D%20%2C%20%5Csqrt%7B6%7D%20%2C%20%5Csqrt%7B39%7D%20%2C%20%5Csqrt%7B89%7D)
Pythagorean Theorem: a²+b²=c²
5²+b²=8²
25+b²=64
<em>Subtract 25 from both sides</em>
b²=39
<em>Square root both sides</em>
b=![\sqrt{39}](https://tex.z-dn.net/?f=%5Csqrt%7B39%7D)
Our answer is ![\sqrt{39}](https://tex.z-dn.net/?f=%5Csqrt%7B39%7D)